Discursos testemunhais midiatizados da Igreja Mundial do Poder de Deus - Vilhagra, Leonardo Teixeira de Freitas Ribeiro (2019)
This work is concerned with the study of testimonial discourses that were published on the website of the World Church of the Power of God. For this purpose, we aim to examine what are the effects of meaning presented in these discourses within a context of institutional dispute in the current Brazilian religious scene. Therefore, we adopted the French Discourse Analysis (AD), as the theoretical-methodological basis, considering the enunciative-discursive perspective proposed by Dominique Maingueneau. In addition, the contributions of Sciences of Religion and Media studies were used in order to support the selected theoretical bases. It’s important to consider that the justification of this work is clear once the resignification of the Neo-Pentecostal doctrine influenced countless churches, among them, the IMPD, which is one of the fastest growing in the last decade, increasing even more its members inside and outside the country. As a result of our analytical course, we found that instead of glorifying God through an account of a person touched by a supernatural event, these new discursive practices end up promoting for the IMPD a marketing based in miracle.